Blood loss in caesarean section in Hospital Universiti Sains Malaysia (HUSM): estimation by surgeons and anaesthetists in comparison with quantitative measurement and blood parameters assessments. - Mohd Ariff, Nazhan Afeef; Ali, Saedah; Ab Mukmin, Laila (Medical Journal of Malaysia, 2017)
Background: We compared the visual estimation of blood loss for Caesarean section (CS) by surgeons and anaethetists and their accuracy with relation to years of experience against quantitative measurement. Haemoglobin (Hb) trend after CS were also studied.